Measuring blood pressure at the wrist: more comfortable for patients and more convenient for doctors? - de Lusignan, S; Thiru, K; Meredith, K; Majeed, A; Johnson, P (2000)
OBJECTIVES: To compare the agreement between conventional measurement of blood pressure and measurements obtained using two automated devices; and to compare how comfortable each of the three methods of measurement were for patients. METHODS: Blood pressure measurements and patient comfort scores were recorded using three different devices in 125-surgery and 40-community patients. The devices used were a conventional aneroid sphygmomanometer, an automated device that measured blood pressure on the upper arm and an automated device that measured blood pressure at the wrist. In each patient, the difference between the conventional and automatic measurement was calculated. The limits of agreement of each device were then calculated as the mean difference +/-1.96 standard deviations. RESULTS: In surgery patients, the width of limits of agreement of wrist measurement were 20.0 mm Hg and 12.1 mm Hg for systolic and diastolic blood pressure respectively, compared with 26. 4 mm Hg and 27.7 mm Hg for automatic arm measurement. In community patients, the width of limits of agreement of wrist measurement were 11.6 mm Hg and 11.0 mm Hg for systolic and diastolic blood pressure respectively, compared with 19.5 mm Hg and 12.1 mm Hg for automatic arm measurement. Surgery patients also reported that wrist measurement of blood pressure was significantly more comfortable than either manual or automatic arm measurement (mean comfort scores 4.03 for automatic wrist and 2.13 for automatic arm measurement, Friedman's Test, P<0.001). CONCLUSIONS: Blood pressure measurements taken using the wrist device agreed more closely with those obtained using a conventional aneroid sphygmomanometer than the arm device. The wrist device was also more comfortable for patients than two other methods of blood pressure measurement. Public Health (2000) 114, 165-168